Cerebral haemodynamics and oxygenation during whole‐body exercise over 5 days at high altitude. Issue 1 (18th February 2020) - Marillier, Mathieu; Rupp, Thomas; Bouzat, Pierre; Walther, Guillaume; Baillieul, Sébastien; Millet, Guillaume Y.; Robach, Paul; Verges, Samuel
Abstract : New Findings: What is the central question of this study? Impairment and subsequent improvement in cerebral oxygenation during acute and prolonged exposure to high altitude affect exercise performance. This study innovates by investigating the effect of acute and prolonged high‐altitude exposure on cerebral haemodynamics during submaximal endurance exercise performed at the same relative intensity. What is the main finding and its importance? Despite exercising at the same relative intensity at sea level and high altitude, participants showed a sustained impairment in cerebral oxygenation after prolonged exposure to high altitude, which might contribute to the absence of improvement in exercise tolerance. Abstract: Deterioration and subsequent improvement in cerebral oxygenation during acute and prolonged hypoxic exposure may affect whole‐body exercise performance at high altitude. In this study, we investigated the effect of hypoxic exposure on cerebral haemodynamics at different cortical locations during exercise at the same relative intensity after 1 (D1) and 5 days (D5) at 4350 m. Eleven male subjects performed a submaximal bout of cycling exercise (6 min at 35% + 6 min at 55% + time‐to‐exhaustion at 75% of peak work rate achieved in the same conditions, i.e. normoxia or hypoxia at sea level) on D1 and D5. Transcranial Doppler and near‐infrared spectroscopy were used to assess middle cerebral artery blood velocity and prefrontal and motor cortex oxygenation, respectively. Despite using the same relative intensity, the duration of exercise was reduced on D1 (22.7 ± 5.1 min) compared with sea level (32.2 ± 9.0 min; P < 0.001), with no improvement on D5 (20.9 ± 6.3 min; P > 0.05). Middle cerebral artery blood velocity during exercise was elevated on D1 (+18.2%) and D5 (+15.0%) compared with sea level ( P < 0.001). However, prefrontal and motor cortex oxygenation was reduced on D1 and D5 compared with sea level ( P < 0.001). This pattern was of similar magnitude between cortical locations, whereas the total haemoglobin concentration increased to a greater extent in the prefrontal versus motor cortex at exhaustion on D1 and D5. In contrast to our primary hypothesis, prefrontal and motor cortex oxygenation and exercise performance did not improve over 5 days at 4350 m. The sustained impairment in cerebral oxygenation might contribute to the absence of improvement in exercise performance after partial acclimatization to high altitude. Abstract :